Phosphodiesterase Type 5 (PDE5) Inhibitors Sensitize Topoisomerase II Inhibitors in Killing Prostate Cancer Through PDE5-Independent Impairment of HR and NHEJ DNA Repair Systems - Chang, Jo-Fan; Hsu, Jui-Ling; Sheng, Yi-Hua; Leu, Wohn-Jenn; Yu, Chia-Chun; Chan, She-Hung; Chan, Mei-Ling; Hsu, Lih-Ching; Liu, Shih-Ping; Guh, Jih-Hwa (Frontiers in Oncology, 2019)
Human castration-resistant prostate cancer (CRPC) is a significant target of clinical research. The use of DNA-damaging agents has a long history in cancer chemotherapy but is limited by their toxicities. The combination with a safer drug can be a strategy in reducing dosage and toxicity while increasing anticancer activity in CRPC treatment. Phosphodiesterase type 5 (PDE5) inhibitors are used to treat erectile dysfunction through the selective inhibition of PDE5 that is responsible for cGMP degradation in the corpus cavernosum. Several studies have reported that PDE5 inhibitors display protective effect against doxorubicin-induced cardiotoxicity. The combinatory treatment of CRPC with doxorubicin and PDE5 inhibitors has been studied accordingly. The data demonstrated that sildenafil or vardenafil (two structure-related PDE5 inhibitors) but not tadalafil (structure-unrelated to sildenafil) sensitized doxorubicin-induced apoptosis in CRPC cells with deteriorating the down-regulation of anti-apoptotic Bcl-2 family members, including Bcl-xL and Mcl-1, and amplifying caspase activation. Homologous recombination (HR) and non-homologous end joining (NHEJ) DNA repair systems were inhibited in the apoptotic sensitization through detection of nuclear foci formation of Rad51 and DNA end-binding of Ku80. PDE5 knockdown to mimic the exposure to PDE5 inhibitors did not reproduce apoptotic sensitization, suggesting a PDE5-independent mechanism. Not only doxorubicin, sildenafil combined with other inhibitors of topoisomerase II but not topoisomerase I also triggered apoptotic sensitization. In conclusion, the data suggest that sildenafil and vardenafil induce PDE5-independent apoptotic sensitization to doxorubicin (or other topoisomerase II inhibitors) through impairment of both HR and NHEJ repair systems that are evident by a decrease of nuclear Rad51 levels and their foci formation in the nucleus, and an inhibition of Ku80 DNA end-binding capability. The combinatory treatment may enable an important strategy for anti-CRPC development.